Second-step lectotypification of Stobaea rigida and reassessment of heterotypic synonyms of Berkheya rigida (Asteraceae, Arctotideae) - Karis, Per Ola; Mckenzie, Robert J. (Phytotaxa, 2024)
As part of a taxonomic reassessment of species that were classified in Berkheya series Rigidae in the most recent monograph of Berkheya, the type material for Berkheya rigida and its putative heterotypic synonyms is reassessed. The original material for the basionym, Stobaea rigida, is heterospecific. Therefore, a second-step lectotype is designated consistent with predominant usage of the name Berkheya rigida. The name Apuleia rigida and its replacement name Stobaea gaertneri apply to a conspicuously radiate species and are excluded from the synonymy of Berkheya rigida. The morphological variability of Berkheya rigida is discussed.